Tectonic-sourced groundwater arsenic in Andean foreland of Argentina: Insight from flow path modeling - Mukherjee, Abhijit; Raychowdhury, N.; Bhattacharya, P.; Bundschuh, J.; Johannesson, K. (2014)
The groundwater arsenic enriched Chaco-Pampean plain of Argentina is located in the active foreland of continental arc dominated Andean orogenic belt. Rhyolitic volcanic glass fragments are a major component of the aeolian-fluvial aquifer sediments, which is dotted with many hot springs that are related to the palaeo-igneous extrusion in the vicinity. Several Salinas in the areas may have originated because of the tectonic evolution of the region. Hydrogeochemical analyses, thermodynamic mixing diagrams and flow path modeling analyses of groundwater samples collected from the Santiago del Estero province suggest that predominant evolutionary processes of the groundwater include chemical weathering with monosialitization silicate of weathering and evaporate dissolution. Anorthite, albite and As-enriched volcanic glass seems to contribute to the major dissolution phases. Subsequently, co-introduced oxyions mobilized the solid-phase As to groundwater by competitive ion exchanged. Further liberation might have taken place by counter-ion activity due to transition of the Ca-rich to Na-rich groundwater due to groundwater mixing with recharged brackish surface water from Salinas or by evaporative concentration due to the prevailing arid climate. © 2014 Taylor & Francis Group.